Kinetics of reductive alkylations of phenylenediamines: influence of substrates isomeric structure - Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Chemical Engineering Science, 2010)
Reductive alkylation of ortho-, meta- and para-phenylenediamines (PDAs) with methyl ethyl ketone (MEK) has been studied in a semi-batch slurry reactor in the presence of a commercial 3% Pt/Al(2)O(3) catalyst. It was observed that the PDA isomers differ remarkably from each other in their activity in reductive alkylation and product distribution. The activity was found to decrease in the following order: PPDA > OPDA > MPDA. To understand the substrate structure-activity correlation, the homogeneous equilibrium reactions involved in the alkylation step and the overall catalytic reactions were studied separately. Kinetics of reductive alkylation of PDAs with MEK as a solvent and alkylating agent with 3% Pt/Al(2)O(3) catalyst was studied in a semi-batch slurry reactor over a temperature range of 373-453K and pressure range of 2.07-6.21 MPa. Semi-batch slurry reactor models were developed and kinetic parameters were estimated by fitting the integral batch reactor data at different temperatures to understand the influence of different reaction steps on the activity and selectivity of different products. Published by Elsevier Ltd.
Keywords: Batch; catalysis; kinetics; Multiphase reactions; Phenylenediamines; Reaction engineering; Reductive alkylation